Evolving character animation - Zakaria, M. Nordin (2001)
This paper describes an approach to the animation of articulated figure using a combination of forward kinematics, neural net and genetic algorithms. A set of kinematics motion data for an articulated model is evolved to generate a set of varied motion that performs according to an objective function set by the user. Neural net is used to constrain the generated motions. User interaction with the process ensures a certain style evolve from the myriad of possibilities. Our technique makes it possible to create libraries of reusable motions from a small number of example motions.